Lower Permian Bryozoa of the Jamal Formation from Bagh-e Vang (Shotori Mountains, northeast Iran) - Ernst, Andrej; Senowbari-Daryan, Baba; Rashidi, Koorosh (Facies, 2006)
Lower Permian Bryozoan fauna of Jamal Formation, exposed in Bagh-e Vang (Shotori Mountains, northeast Iran) includes six species. Three species - Streblotrypa (Streblascopora) marmionensis (Etheridge 1926), Rhabdomeson bispinosum (Crockford 1944) and Alternifenestella kungurensis (Stuckenberg 1898) - indicate the Lower Permian (Artinskian to Kungurian) age of the formation. Three additional taxa - Fistulipora sp. 1, Fistulipora sp. 2 and undetermined timanodictyid bryozoan? Timanodictya sp. could not be identified at the species level. The investigated fauna refers to Uralian and Australian palaeobiogeographic provinces. © Springer-Verlag 2006.
UnivIS-Import:2017-11-07:Pub.2006.nat.dgeo.IGM.LP.lowerp
Keywords: Bryozoa; Iran; Jamal Formation; Lower Permian; Palaeo geography; Shotori Mountains; Systematics